ANALISIS TINGKAT PENGGUNAAN PUPUK ORGANIK PADA USAHATANI PADI DI KABUPATEN LOMBOK BARAT: Analysis Of The Level Of Organic Fertilizer Use In Rice Farming In West Lombok District - FR, Aeko Fria Utama; Fadli, Fadli (Ganec Swara, 2025)
This study aims to determine the motivation of farmers in using organic fertilizers in rice farming in West Lombok Regency and to determine the level of use of organic fertilizers used by farmers in rice farming in West Lombok Regency. The method used in this study is a descriptive method. The unit of analysis in this study is rice farmers in Narmada District, West Lombok Regency. While the location of the study in 3 villages in Narmada District, West Lombok Regency, namely Respondents in this study were determined as many as 40 respondents, This study consists of 2 types of data, namely quantitative data and qualitative data and there are 2 data sources, namely primary data and secondary data. While the analysis used to determine the motivation of farmers in using organic fertilizers in rice farming is to use the scoring method. The level of farmer motivation in using organic fertilizers in rice farming is analyzed using a scoring system, namely respondents who have high motivation in using organic fertilizers in rice farming are given a score of 3 (three), farmers who have moderate motivation are given a score of 2 (two) and farmers who have low motivation are given a score of 1 (one). The results of the study showed that the level of farmer motivation in the use of organic fertilizer in rice farming in Narmada District, West Lombok Regency was included in the moderate category with 18 (45%) farmers having high motivation, and 21 (52.5%) farmers having moderate motivation, and 1 (2.5%) farmer having low motivation